An Analysis of Hate Speech Targeting an Overweight Transgender Individual on TikTok Comments: A Case Study of @al.weeezy - Mareta Putri Hariyanto; Endah Alamsari; Yudy Prasetyo (Journey: Journal of English Language and Pedagogy, 2026)
Hate speech is now increasingly visible along with the increase in the use of social media specifically on TikTok where the comment column is often a space for language that demeans marginalized individuals. In response to growing concerns related to intersectional discrimination in digital communications, this study conducted a study of online hate speech aimed at overweight transgender content creators. This study aims to identify the types of hate speech with communicative intent contained in English TikTok comments. This study uses a qualitative descriptive method where as many comments have been collected on the TikTok account @al.weeezy from October to December 2024. In this dataset, where 28 comments containing expressions of hate have been selected to conduct an in-depth analysis based on the compatibility of the hate speech indicators, so that in order to ensure the validity of the data, the comments were carefully examined by being categorized according to explicit linguistic features by associating with hate speech so that this analysis determined the grouping of the types of hate speech expressed by Mondal et al. with a framework that has communicative intentions according to Kreidler. The results of the study indicate that hate speech about physical appearance is the most dominant type followed by attacks that target behavior with gender identity so that in terms of communicative, mocking and insulting can be interpreted as the most often used strategy in expressing hostility so that this result indicates that transphobia with body-shaming that has interaction with each other in discourse online by creating a layered form of discrimination so that in this study it can contribute to pragmatic and sociolinguistic analysis by emphasizing how linguistic strategies are used to build hate speech in digital communication and emphasizing the importance of encouraging more inclusive and responsible online interactions.